Design and Development of Smart Basnet Applications as a Basic Network Learning Media for First Grade Student of Vocational High School - Putri, Rena Anggita; Hatta, Puspanda; Tamrin, A.G. (IJIE (Indonesian Journal of Informatics Education), 2017)
The lack of adequate learning resources has an impact on the low level of student interest in the subject matter, resulting in disruption of the process to achieve the expected learning objectives. The development of technology, can be used to design an application that can be used as a source of learning or learning media. The purpose of this research is to produce application product learning that can be used as learning media for basic network subjects. The development model used is the development model of ADDIE, which is analisys, design, develop, implementation, and evaluation. Data collection techniques used were observation, literature, documentation, and questionnaires. Applications tested up to 35 students of class X TKJ. The results of the validation learning application obtained a percentage of 93.4% of media experts, 88.8% of materials experts and 81.2% of users or students. Indicates that learning applications that have been developed can be used as learning resources or learning media for basic network subjects.Keywords: Learning Application, Basic Network, Computer and Network Engineering